WAYS TO IMPROVE THE EFFICIENCY OF INNOVATIONS IN THE MODERNIZATION OF THE ECONOMY (Academicia Globe: Inderscience Research, 2023)
The article opened a new page in the development of the national economy. Countries at different points in economic development have their own characteristics in the allocation of general social income. In addition to the development of bad relationships and the formation of high industrial resources, there is a need to broadly explain the concepts of "investment" and "investment process" .